KØBENHAVN - Anderson, Sally (Tidsskriftet Antropologi, 2003)
Copenhagen is the capital of Denmark and the Kingdom’s only metropolis. The city embraces institutions of royalty, state and national culture as well as all the ‘people’ of Denmark. Whereas national institutions are by and large located within the walls of the fortress city, the ‘people’ are generally located in neighborhoods constructed during rapid industrialization. The article explores the idea of Copenhagen as a folkelig city, a city that accrues both legitimacy and authenticity by invoking the ‘people’ in all their social, regional and ethnic diversity in certain areas of the city. Although a down-to-earth, non-elite, folkelig community is commonly thought to derive from the daily lives of ‘common people’ in lower class neighborhoods, the article illustrates how the idea of folkelig community is intentionally evoked in efforts to revitalize such very neighborhoods deemed lacking a proper sense of community. The article discusses how two voluntary organizations run by middle class reformers invoke different aesthetics of diversity and authentic commonality in attempts to infuse a working class neighborhood undergoing urban renewal with a new sense of folkelig community. With each their own facility for voluntary sport and culture, both aspire to create venues promoting a common sociality that cross cuts social difference. While the locally based organization invokes a plural community of locals, the nationally based organization invokes a plural community of citizens. The article concludes that the aesthetic of common diversity and the performance of folkelig community are vital to the ideal of the good city upheld by Copenhagen’s mentors, organizers and authorities.